Un caso-estudio sobre las revistas educativas: La Revista Educación (Género y producción de conocimiento). - Mª Yolanda Aguilera Alonso (Universidad Complutense de Madrid, 2006)
Published articles on "Revista de Educación" between 1952 and 2000 are analysed from gender point of view. In a feminised world as educational action is, this investigation shows an andocentric magazine due to most articles have men as authors and very few articles talks about women and/or feminism. Over educational system this paper verifies that traditional social sex roles still maintains keeps on, assigning women executing work while creation and management belongs to men. Women difficulties accessing to knowledge production it's being resists by masculine academic power.